Sensor eletroquímico à base de carbon black super-P e ftalocianina de cobalto para detecção de L-cisteína - MOUCHREK, Charbel Nagib (2023)
In this work, was produced a novel composite material using carbon black and cobalt phthalocyanine (CoPc/CBSP). Characterizations by spectroscopic techniques (Raman and infrared), scanning electron microscopy, and X-ray diffraction confirmed the formation of the composite material. This material was anchored on the glassy carbon electrode surface, and its electrochemical sensing properties was checked using cysteine (CYS), an important amino widely used in medicine, food additives, and cosmetics, as a model molecule. Preliminary studies by cyclic voltammetry revealed that the modified electrode caused considerable electrocatalytic effects (detection at potential close to 0 V) and an increase in peak current (12-fold) compared to the unmodified electrode. When coupled to the BIA analysis system with amperometric detection, a wide linear range (1 ‒ 150 μmol L−1 ) and adequate detectability (LOD = 0.133 μmol L−1 ) were achieved. Repeatability tests (n = 20) at two concentration levels (20 and 40 μmol L−1 ) confirmed the precision of the method (RSD < 11%). To evaluate the reproducibility of sensor preparation, four different electrodes were tested against a 40 μmol L−1 concentration solution and produced an error of 13.5%. The proposed method was applied for the determination of CYS in pharmaceutical samples, where addition/recovery studies (values between 89 and 110%), as well as results statistically similar to those achieved by capillary electrophoresis, indicated the accuracy and reliability of the electrochemical analyses.